2015
DOI: 10.1063/1.4935578
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra of azaindole and its excited state mixing: A symmetry-adapted cluster configuration interaction study

Abstract: Articles you may be interested inElectronic spectra and photodissociation of vinyl chloride: A symmetry-adapted cluster configuration interaction study J. Chem. Phys. 124, 034312 (2006) Electronic spectra of azaindole and its excited state mixing: A symmetry-adapted cluster configuration interaction study Electronic structures of azaindole were studied using symmetry-adapted cluster configuration interaction theory utilizing Dunning's cc-pVTZ basis set augmented with appropriate Rydberg spd functions on carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The patterns of the L a and L b states for the set of Scheme are less systematic than in the oligoacene series. The presence of heteroatom(s) induces some variations on the nature of the ππ* transitions, such as character mixing with nearby πσ* and nπ* states, or between the L a and L b states . For compound VIII, a moiety frequently found in organic electronics, there is even an ambiguity in determining the character of L a and L b since both states belong to the same irreducible representation and, therefore, mix (see the SI for the assignment used herein).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patterns of the L a and L b states for the set of Scheme are less systematic than in the oligoacene series. The presence of heteroatom(s) induces some variations on the nature of the ππ* transitions, such as character mixing with nearby πσ* and nπ* states, or between the L a and L b states . For compound VIII, a moiety frequently found in organic electronics, there is even an ambiguity in determining the character of L a and L b since both states belong to the same irreducible representation and, therefore, mix (see the SI for the assignment used herein).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, the L a -L b problem originates from the description of both states. Indole (a building block of tryptophan amino acid) and several structurally related compounds were found to behave similarly. Indeed, it was shown that both hybrid and meta -GGA functionals predict a wrong ordering of the L a and L b ππ* states, whereas range-separated hybrid functionals, despite providing a qualitatively correct ordering of the states, predict much too small energy gaps compared to the experimental values. The inversion of the L a and L b states was also spotted for 9H-adenine by comparing TD-DFT estimates to high level reference values obtained with wave function-based approaches, such as EOM-CCSD­(T) (equation of motion-coupled cluster singles and doubles with perturbative triples) or CASPT2 (complete active space second-order perturbation theory), even though the ambiguity still remains in this case .…”
Section: Introductionmentioning
confidence: 99%
“…1 for the atom numbering) are excellent blue emitters for organic lightemitting diodes (OLEDs). 4 Although one can find a handful of articles on 7-azaindole as an isolated monomer, [5][6][7][8] in dimeric forms 5,[9][10][11][12][13] and in water and alcohol clusters, 11,[14][15][16][17][18][19][20] only one recent article 21 to date shed light upon the photophysical relaxation mechanism of nazaindole molecules by studying gas-phase excited-state dynamics. Experiments and theoretical calculations have also been devoted 16,18,[22][23][24] to understanding the excited-state proton transfer and tautomerization mechanism of 7-azaindole with solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental spectral width and derived lifetimes of n-AIH + isomers from Ref. 25 Although one can find a handful of articles on 7-azaindole in isolated monomer, [5][6][7][8] in dimeric forms 5,[9][10][11][12][13] and water and alcohol clusters, 11,[14][15][16][17][18][19][20] only one recent article 21 to date shed light upon the photophysical relaxation mechanism of n-azaindole molecules by studying gasphase excited-state dynamics. Experiments and theoretical calculations have also been devoted 16,18,[22][23][24] to understanding the excited-state proton transfer and tautomerization mechanism of 7-azaindole with solvent molecules.…”
Section: Introductionmentioning
confidence: 99%